DESAIN DIDAKTIS PADA KONSEP LUAS PERMUKAAN PRISMA DENGAN PEMBELAJARAN MATEMATIKA REALISTIK DI KELAS VIII SMP - Fatimah, Lia Arsy (2017)
The research is titled "Dictatical Design on the Concept of Surface Prism Area with Realistic Mathematics Education in Class VIII Junior High School" aimed at designing didactic design on the concept of surface area of prism in class VIII using realistic mathematics eduaction. The didactic design is based on learning obstacle that are epistemological obstacle, didactical obstacle, and ontogenic obstacle occurring during preliminary research. Epistemological obstacle found in the form of limited understanding of students on the concept of the surface area of the prism. Didactical obstacles are found in the form of learning path problems and approaches to teaching teachers structurally (conceptual interrelationship) and functional (continuity of thinking). Ontogenic obstacles found in the form of lack of understanding of prerequisite materials to understand the concept of the surface area of the prism. Therefore, researchers designed a didactic design using realistic mathematics eduaction to help students overcome learning obstacle experienced in understanding the concept of the surface area of the prism. This research includes qualitative research in the form of Didactical Design Research. Preliminary research was conducted on the students of class IX as many as 100 students and the implementation of didactic design done on the students of class VIII B for 4 meetings in one of the same Junior High School Bandung. The results show that didactic design using realistic mathematics eduaction can minimize the learning obstacle experienced by students.---- Penelitian ini berjudul "Desain Didaktis pada Konsep Luas Permukaan Prisma dengan Pembelajaran Matematika Realistik di Kelas VIII SMP" yang bertujuan untuk merancang desain didaktis pada konsep luas permukaan prisma di kelas VIII menggunakan pembelajaran matematika realistik. Desain didaktis disusun berdasarkan learning obstacle yaitu epistemological obstacle, didactical obstacle, dan ontogenic obstacle yang terjadi pada saat penelitian pendahuluan. Epistemological obstacle yang ditemukan berupa terbatasnya pemahaman siswa pada konsep luas permukaan prisma. Didactical obstacle yang ditemukan berupa permasalahan alur belajar dan cara pendekatan mengajar guru secara struktural (keterkaitan konsep) dan fungsional (kesinambungan berpikir).Ontogenic obstacle yang ditemukan berupa kurangnya pemahaman materi prasyarat untuk memahami konsep luas permukaan prisma. Oleh karena itu, peneliti merancang desain didaktis menggunakan pembelajaran matematika realistik untuk membantu siswa mengatasi learning obstacle yang dialami dalam memahami konsep luas permukaan prisma. Penelitian ini termasuk penelitian kualitatif berupa Didactical Design Research. Penelitian pendahuluan dilakukan pada siswa kelas IX sebanyak 100 orang siswa dan implementasi desain didaktis dilakukan pada siswa kelas VIII B selama 4 pertemuan di salah satu SMP Negeri Bandung yang sama. Hasil penelitian menunjukkan bahwa desain didaktis menggunakan pembelajaran matematika realistik dapat meminimalkan learning obstacle yang dialami siswa.